1980
DOI: 10.1104/pp.66.4.704
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of a Mitochondrial Function by Oat Phytochrome in Vitro

Abstract: ABSTRACTresponses of these organelles to actinic R2 and FR were the earliest extensively studied correlations between these two phenomena. In the present paper, we are reporting our tests of whether Manabe and Furuya's results with pea mitochondria can be obtained with oat mitochondria. We also describe tests of whether exogenously added phytochrome, previously shown to bind to mitochondria with a reproducible stoichiometry (12), could influence the activity of the external NADH-dehydrogenases of mitochondria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The control of Ca2+ fluxes in mitochondria by phytochrome may be related to its control of a mitochondrial enzyme, NADH dehydrogenase, reported by Cedel and Roux (6). This enzyme is located on the outer surface of the inner membrane of mitochondria, and its activity is strongly stimulated by added Ca2' (21).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…The control of Ca2+ fluxes in mitochondria by phytochrome may be related to its control of a mitochondrial enzyme, NADH dehydrogenase, reported by Cedel and Roux (6). This enzyme is located on the outer surface of the inner membrane of mitochondria, and its activity is strongly stimulated by added Ca2' (21).…”
Section: Resultsmentioning
confidence: 89%
“…The experiments in ref. 6 an electrochemical gradient (i.e., from inside the mitochondrial matrix to the outside). This movement, just as the Pfr-promoted Ca2+ movement across the plasma membrane, would promote an increased Ca2+ concentration in the cytosol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phytochrome system may regulate mitochondrial respiration through both kinetic mechanisms and modification of gene expression. Cedel & Roux (,) showed that phytochrome could alter the rate of reduction of exogenously added NADP + by plant mitochondrial preparations. Such interaction between phytochrome and mitochondria occurred at the level of the inner mitochondrial membrane and could be seen only if the mitochondria were isolated from plants that were illuminated with white or red light before extraction.…”
Section: Phytochrome Regulation Of the Tricarboxylic Acid (Tca) Cyclementioning
confidence: 99%
“…Given the relatively low number of high affinity sites for phytochrome in the mitochondrial preparation, any amount of contaminant membrane would compromise the confident identification of the binding site, if this identification were based solely on the purity of the preparation. A more important basis for identifying mitochondria as a probable binding site for 125I-P in the data reported here is the fact that exogenously added phytochrome photoreversibly alters a mitochondrial function, NADHdehydrogenase, under the same experimental conditions as used for these binding studies (3). These physiological data in combination with the data in Table II argue strongly for the working hypothesis of this report: That the specific binding of '25I-P to sites in the mitochondrial membrane preparation was to sites on the mitochondria in the preparation.…”
Section: Methodsmentioning
confidence: 91%